Síntese, caracterização e estudo das propriedades eletrônicas de heterocomplexos formados por 4, 4’, 4”, 4’’’, tetrassulfoftalocianina de cobalto (II) e tetrakis(N-metil-4- piridil)porfirina de cobalto (II) e formação de filmes Layer-by- Layer - Tasso, Thiago Teixeira (Universidade Federal de São Carlos, 2011)
This work reports the synthesis, characterization and investigation of the electronic properties of heterocomplexes formed by cobalt(II) tetrakis(N-methyl-4- pyridyl)porphyrin (CoTMPyP) and cobalt(II) 4, 4 , 4 , 4 , tetrasulfophtalocyanine (CoTsPc) in solution and thin films. Spectroscopic titrations were performed using solutions of the CoTsPc and CoTMPyP macrocycles, and the heteroaggregates stoichiometries were investigated using Job s method. The Job s plots pointed to the formation of supramolecular arrays containing higher proportions of CoTsPc. It was possible, for the first time, to isolate species formed in solution by changing the medium s dielectric constant. After characterization of the isolated species, it was verified that, despite the different stoichiometries, only one heterocomplex was formed, composed by two molecules of CoTsPc in terminal positions and one CoTMPyP molecule. The triad was characterized by mass spectrometry and UV-vis and i.v. absorption spectroscopy. Strong interactions between the charged substituent groups of the CoTsPc and CoTMPyP macrocycles were observed, in addition to the significant changes on the macrocycles electronic levels, due to the coupling of the electronic densities in the face-to-face array. Thin films containing the precursor macrocycles and the triad were grown using the Layer-by-Layer (LbL) technique. LbL films of CoTsPc with poly(allylamine hydrochloride) (PAH) polymer and CoTMPyP with poly(styrenesulfonate) (PSS) polymer were grown up to 30 bilayers. The CoTsPc and CoTMPyP macrocycles, in the mixed LbL films, behave independently, without formation of heteroaggregates during bilayers deposition. Triad s LbL films, using PAH as polyelectrolyte, were also obtained up to 15 bilayers. Cyclic voltammetry measurements of the LbL films demonstrated the coupling of the macrocycles electronic densities in the triad, through changes in the redox potential of both rings and metallic centers.
Synthesis, characterization and study of the electronic properties of heterocomplexes formed by cobalt(II) 4, 4’, 4”, 4’’’, tetrasulfophtalocyanine and cobalt(II) tetrakis(N-methyl-4-pyridyl)porphyrin and Layer-by-Layer films formation
Keywords: Química inorgânica; Porfirina e compostos de porfirina; Ftalocianina de cobalto; Química supramolecular; Propriedades eletrônicas; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA